Microstructure and mechanical properties of diffusion bonded W/MA956 steel joints with a titanium interlayer by SPS - Kong, Weiqing (2020)
Diffusion bonding is an effective technique for joining dissimilar metals. In this paper, tungsten and MA956 steel were diffusion-bonded by Spark Plasma Sintering (SPS) technique with titanium (Ti) foil as an interlayer. The bonded joints were evaluated by metallographic analysis and mechanical tests, and the results reveal that all W/Ti/MA956 joints were well bonded by efficient SPS technique. Microstructure analysis showed that W-Ti solid solution formed at W/Ti interface; reaction phases at Ti/MA956 steel interface varied with the joining temperature, e.g. intermetallics phases FeTi for 850 °C, FeTi, Fe2Ti and Cr2Ti for 900 °C and 950 °C joining temperature. The peak value of microhardness occurred at the interfaces of Ti/MA956 steel owing to the formation of intermetallic compound. All specimens of shear testing fractured at the Ti/MA956 steel interface close to MA956, and the average shear strength of joints was 182 MPa, 228 MPa and 164 MPa bonded at 850 °C, 900 °C and 950 °C respectively.